Therapeutic Potential of TPT-260 in Ischemic Stroke: An Investigation Into Its Anti-Inflammatory Effects and Impact on Microglial Activation - Qian J; Guo X; Xu Q; Huang Z (Journal of Inflammation Research)
Jun Qian,1 Xiaoming Guo,2 Qian Xu,1 Zhidong Huang1 1Department of Rehabilitation Medicine, Affiliated Hospital 2 of Nantong University, Nantong, People’s Republic of China; 2Department of Neurology, Affiliated Hospital 2 of Nantong University, Nantong, People’s Republic of ChinaCorrespondence: Jun Qian, Department of Rehabilitation Medicine, Affiliated Hospital 2 of Nantong University, No. 666, Shengli Road, Chongchuan District, Nantong City, Jiangsu, 226009, People’s Republic of China, Email qjjianggushi@163.comBackground: Ischemic stroke is characterized by a high incidence and elevated mortality. Ischemic events trigger neuroinflammation, leading to severe brain edema and neuronal necrosis. Microglia are the primary mediators of neuroinflammation. Inhibition of M1 microglia effectively alleviate neuronal damage in mild stroke. TPT-260 is a minimally cytotoxic, small molecule chaperone of the retromer complex, which mediates the recycling and trafficking of membrane protein receptors. This study explores the therapeutic effects and related mechanisms of TPT-260 in stroke model mice from an anti-inflammatory perspective, aiming to evaluate the efficacy and mechanism of TPT-260 in treating stroke.Methods: In this study, a middle cerebral artery occlusion (MCAO) animal model was established to simulate ischemic stroke. Primary microglia were cultured for lipopolysaccharides treatment to construct M1 microglia. Both animals and cells were treated with TPT-260. Nuclear factor-κB (NF-κB) nuclear translocation and the expression of downstream pro-inflammatory factors Interleukin 1β (IL-1β) and Tumor necrosis factor-α (TNF-α) were determined.Results: In vivo results revealed that TPT-260 significantly reduced the brain infarct area and inflammation as well as improved the neurological function of the stroke model mice. The potential mechanism of TPT-260 involved the marked inhibition of the lipopolysaccharides-induced M1 microglia by suppressing NF-κB nuclear translocation and attenuating the expression IL-1β and TNF-α. Moreover, TPT-260 inhibited NOD-like receptor protein 3 and reduced inflammasome formation, thereby decreasing the release of mature IL-1β and alleviating neuroinflammation.Conclusion: TPT-260 attenuated M1 microglia via repression of NF-κB signaling, thus preventing neuroinflammation and neuronal injuries in stroke model mice.Keywords: TPT-260, ischemic stroke, microglia, NF-κB, inflammation